La continencia aristotélica : encauzamiento de las acciones rectas en el científico que experimenta con animales. (2014)
In Aristotelian ethics, the virtue of continence is responsible for mastering the soul and direct it towards the right reason; thus the continent, knowing that passions are bad does not follow them because of the reason; this virtuous is the one who subdues the passions, since both, reason and passions, oppose each other. For Aristotle the desire is the beginning of the action, followed by the discussion leading to choose the best and the most perfect virtuous action. It is important for bioethics that the virtue of continence applies to the actions of scientists who use animals for experimentation and that all their actions are mediated by the good actions. This article will deal with the virtue of continence as the channeling of actions mediated by right reason in the scientist who is experimenting with animals.